COURSE ENJOYMENT AND LEARNING STYLE OF PARTICIPANTS OF A DISTANCE LEARNING PROGRAM IN HEALTH PROFESSIONS EDUCATION (HPE): A Distance Learning Program in Medical Education - Sadia, Shamsunnisa; Ashar, Abid; Ahmad, Amina (Pakistan Armed Forces Medical Journal, 2016)
Objective: To identify and relate enjoyment levels of various components of MCPS-HPE course and the learning styles of the course participants followed by explanation of the reasons for enjoyment, non-enjoyment and how enjoyment factors can be enhanced.Study Design: Mixed method sequential study.Place and Duration of Study: College of physicians and surgeons, Pakistan, Regional Center, Lahore from January 2013 to April 2014.Material and Methods: Learning style of MCPS-HPE course participants of 2011-13 batch was identified through Kolb’s Learning Style Inventory version 3.1; and participant’s perception of the most enjoyable areas in the contact sessions and assignment completion were sought on two respective survey forms followed by structured interviews. Analysis of the quantitative data was performed using SPSS version 19. “Framework method” was used for the manual analysis of qualitative data.Result: Learners identified social interaction, team work, knowledge construction, active learning and selfefficacy as enjoyable while cognitive overload, disruptions in learning, and deadlines as factors impeding enjoyment. Acquiring learning skills, contextual simplified learning, addressing disruptions and promoting active learning and proactive mentorship were suggested as measures for improving enjoyment level. Predominantly our participants were convergers who enjoyed the course more than those with other learning styles.Conclusion: Team work along with experiential learning improves learners’ self-efficacy and enthusiasm. Ensuring contextual learning and proactive mentoring can address negative impact of cognitive overload, inappropriate facilitator’s attitude and deadlines on course enjoyment while taking into account various learning styles.